Analisis Pengendalian Kualitas Produk Dengan Metode Six Sigma dan TRIZ Untuk Mengurangi Jumlah Kecacatan Produk Di UD Cantenan - Ndoro Jatun Kuncoro Jakti; Ari Zaqi Al Faritsy (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2024)
Abstract. UD Cantenan is an industrial company engaged in metal casting, especially made from Aluminum. This company is known to have quality control problems in the manufacture of lip handle products and canal parts. The result of this problem is defective products in the lip handle and canal parts. In this case, of course, the company will spend more to repair the product so that the company experiences losses. Companies need to find ways to reduce the number of defective products. In this study, the Six Sigma method was used with DMAIC (Define, Measure, Analyze, Improve Control) and TRIZ stages to analyze and provide solutions to improve problems that occurred in the company. Based on the research conducted, at the define stage there are 3 types of defects in the lip handle product and canal parts, namely small scratches, small pinholes, and asymmetrical patterns. Then the measure stage obtained the percentage of small scratch defects of 54.47%, small pinholes of 17.3% and asymmetrical patterns of 28.2%. The average DPMO score obtained is 25,720 with a sigma level of 3.45 which shows that UD Cantenan can be categorized as good for industry in Indonesia. Furthermore, at the analysis stage Based on the identification of causal factors using FMEA analysis, it is known that the biggest contributing factor to failure is operator error in the operation of the milling machine. Then at the improve stage, make improvement proposals based on obtaining the highest RPN value from the factors causing disability using the TRIZ method. And the last stage, namely control, is the result of proposed improvements that can be made by the company to solve problems to reduce the number of product defects that occur during the production process.